The analysis of wood harvesting restrictions in conservation areas and old-growth forests of the Arkhangelsk oblast - Gerasimov, Yuri; Markovsky, Alexander; Dobrynin, Denis; Ilina, Olga (Finnish Forest Research Institute, 2007)
Analysis of the current state and wood harvesting restrictions in officially existing and planned conservation areas as well as unofficial old-growth forests of the Arkhangelsk oblast is provided in this report. Old-growth forests are suggested by NGOs and these forests do not have wood harvesting restrictions according to the Russian legislation. However, environmentally responsible forest industries companies do not procure wood from these forests.In the beginning July 2007, Arkhangelsk oblast has 110 official conservation areas with a total area of 6.5 million ha. However, several reserves, such as the large reserve Frants-Iosif Land located in Baretsevo sea islands, are out of forest fund of Arkhangelsk oblast. The total area of the forest-related conservation areas is 2.2 million ha (7.6% of the total forest fund of Arkhangelsk oblast). All types of fellings are prohibited in 11 official conservation areas (0.6 million ha or 2.1% of the forest fund of Arkhangelsk oblast). Final fellings (or clearcut) are prohibited in 51 official conservation areas (1.6 million ha or 5.4% of the forest fund of Arkhangelsk oblast). The rest of the conservation areas (30400 ha or 0.1% of the forest fund of Arkhangelsk oblast) have no restrictions for wood harvesting. Two officially planned conservation areas (5.3 million ha) have been clearly recognized; however only the Onezhskoye Pomorye national park (180400 ha or 0.6% of the forest fund of Arkhangelsk oblast) is located within forest fund of the region and has restrictions for wood harvesting. NGOs have suggested 11 separate areas of old-growth forests (approximately 9.5 million ha or 32.4% of the forest fund of Arkhangelsk oblast). The major areas of old-growth forests are located in Leshukonsky, Mezensky, Severodvinsky, Onezhsky, Karpogorsky, Krasnoborsky, Pinezhsky, Priozerny, Sursky, Vyisky and Bereznikovsky leskhozes. Locations of conservation areas and old-growth forests are shown in the whole Arkhangelsk oblast, at forest district ( leskhoz ) and at forest block ( ...